Engineering a homochiral metal–organic framework based on an amino acid for enantioselective separation. Issue 63 (8th July 2020) - Tang, Haitong; Yang, Keke; Wang, Kun-Yu; Meng, Qi; Wu, Fan; fang, Yu; Wu, Xiang; Li, Yougui; Zhang, WenCheng; Luo, Yunfei; Zhu, Chengfeng; Zhou, Hong-Cai
Abstract : A homochiral metal–organic framework is constructed from an amino acid-derived ligand and it exhibits high enantioseparation capacities for alcohols, epoxides, and ibuprofen. Abstract : A chiral metal–organic framework possessing an open amphiphilic channel is constructed from a dicarboxylate ligand derived from an amino acid and is shown to be an efficient and recyclable chiral solid adsorbent, which is capable of separating racemic secondary alcohols, epoxides, and ibuprofen with very high enantioselectivity.